Linking Top-Down and Bottom-Up Models for Climate Policy Analysis : The Case of China - Timilsina, Govinda; Pang, Jun; Yang, Xi (World Bank, Washington, DC, 2019)
Top-down economic models, such as computable general equilibrium models, are the common tools to assess the economic impacts of climate change policies. However, these models are incapable of representing the detailed technological characteristics of the sources of greenhouse gas emissions. The economic impacts measured by the top-down economic models are likely to be overestimated. This study attempts to quantify the overestimation by measuring the economic impacts linking the top-down model with a bottom-up engineering model for the energy sector. The study uses meeting China's pledges under the Paris Agreement for testing this hypothesis. The study shows that the economic impacts measured by the stand-alone top-down model are almost three times as high as those resulting from the model after linking it with the bottom-up model. However, the findings are sensitive to the assumptions and existing or planned policies on energy technologies considered in the bottom-up model.